The Genies of the Northwest Palace of Assurnasirpal II - Portuese, Ludovico (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
The doors and gates of the Northwest Palace of Assurnasirpal II at Kalhu were highly guarded by a great variety of protective figures, known as genies. Their protective role derives not only from their simple presence, but also from apotropaic objects they hold: ritual buckets, pinecone-shaped objects, maces, various species of plants, deer, goats, kids, and lambs. From the presence of these assorted attributes, one may deduce that doorways provided not only the settings for ritual activities, but were themselves recipients of and/or participated in actual rituals. On this premise, the article analyses the protective figures and their attributes in the light of textual references in Mesopotamian incantations, rituals and medical prescriptions in order to re-create apotropaic rituals performed at doorways in the palace. Additionally, a link between ritual activity and internal movement will be proposed, thereby assigning specific doors to individual groups of people circulating within the palace. The analysis concludes that rituals and protective figures cooperated to protect the palace and were meant as strategies to cope with collective fear.